Happiness depends on the neighborhood: Spanish journals as source publications in Web of science - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2011)
This paper analyzes the situation of Spanish journals in the master journal list of ISI Thomson Reuters´ citation indexes. The changes since 2007 will influence future results of bibliometric indicators of Journal Citation Reports. The presence of Spanish journals has increased significantly, especially in Social Sciences, where it started from a situation of invisibility. However, there are two important constraints in this success: the percentage of Spanish publications remains very limited and not all scientific fields will benefit equally from this progress.